A RESTORATIVE JUSTICE APPROACH IN THE IMPLEMENTATION OF THE JUVENILE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Ahmad Novaisal; Ferry Irmawan; Riki Hamdani; Sony Prayudha Winata; Syaiful Asmi Hasibuan (PT. Radja Intercontinental Publishing, 2023)
Since the enactment of Law no. 11 of 2012 concerning the Juvenile Criminal Justice System in Indonesia, it is necessary to immediately provide outreach to Law Enforcement Officials (APH) who do not yet understand and know about the obligation to take a restorative justice approach in the implementation of the Juvenile Criminal Justice System. The norms governing the obligation to carry out a restorative justice approach in handling children in conflict with the law (ABH) are contained in article 5 paragraph 1 of the Juvenile Criminal Justice System Law and this law has also adopted the International Convention on the Rights of the Child (CRC) instrument which has been adopted. ratified by the government of the Republic of Indonesia with Presidential Decree Number 36 of 1990 concerning Ratification of the Convention on the Rights of the Child (Convention on the Rights of the Child) in addition to other international regulations such as the Beijing Rules, Riyadh Guidelines and Tokyo Rules which are of course in line with the Constitution 1945 concerning the goals of the state, one of which is to realize social justice and promote general welfare. This restorative justice approach certainly has the same spirit as the ideological, political and socio-cultural values ​​of the Indonesian nation which prioritizes resolution through deliberation to reach consensus so that this restorative justice approach is also one of the legal reforms that further promotes the values ​​of local wisdom of the nation. Indonesia. The conceptual approach and the statutory approach are the approaches used in this research and maximize the implementation of the implementation of restorative justice in every handling of Children in Conflict with the Law (ABH) at every stage of the investigation, prosecution and trial process. Objectives The aim of the research is to provide confirmation to every Law Enforcement Officer of the obligation to take a Restorative Justice approach in every handling of ABH.